Integrasi Layanan Bimbingan Karier Mata Pelajaran IPS SMP - Lisawati, Dwi Meliana; Ismaya, Erik Aditia (Peneliti.net, 2024)
This research aims to find out whether career guidance services can be integrated into social studies subjects. The research method used is a qualitative approach with a classroom action research design. This classroom action research collaborates with guidance and counseling teachers. This research design includes several stages, namely mapping competency standards for social studies subjects related to career awareness and mapping competency standards for career guidance for junior high school classes, preparing learning materials, preparing action plans, training teachers in carrying out learning, implementing actions, results of implementing actions, and evaluation and discussion. This research was carried out in two cycles with collaboration between researchers and teachers. The researcher himself is the key instrument in collecting, analyzing and concluding data. The data collection techniques used are observation and recording. Data analysis was carried out using a flowing data analysis model which includes data reduction, data presentation, verification and data conclusion stages. To maintain the validity of the data, triangulation and peer checking were carried out. The research results show that career guidance services can be integrated into social studies subjects. Of the 32 students at SMP 2 Jekulo Kudus, 85% of students were able to answer questions related to career guidence.